Gender differences in in-hospital mortality and angiographic findings of patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) - Zanchi, Jakša (Array, 2009)
Abstract: There are conflicting reports in the literature regarding the role of sex on the in-hospital mortality of patients with acute myocardial infarction. The objective of this study is to determine whether there are gender differences in in-hospital mortality and angiographic findings of patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). We conducted a prospective study of all patients admitted to University Hospital Center Split, Croatia with STEMI from 2004 to 2008 who underwent PCI. From March 2004 throughout September 2008, 488 patients with STEMI underwent PCI (364 men, 74.6%; 124 women, 25.4%). Compared with men, women were significantly older (mean age, 67.3 vs. 60.3 years; p<0.001). Men had a significantly higher proportion of circumflex artery occlusion (19.5% vs. 10.5%, p=0.022). A higher proportion of men had a multivessel disease than women (56.8% vs. 41.9%; p=0.004). In-hospital mortality was significantly higher among women (11.3% vs. 4.6%; p=0.002) but after adjustment for the baseline difference in age, the female sex was not an independent predictor of in-hospital mortality (adjusted OR 1.15; 95% CI 0.82–1.84). In men, occlusions of left anterior descending artery showed higher mortality rate than occlusions of other coronary arteries (LM 0%, LAD 7.3%, Cx 2.8%, RCA 0.7%, p=0.03). According to our results female gender is not an independent predictor of in-hospital mortality after percutaneous coronary intervention. In men, occlusions of left anterior descending arteries are associated with higher mortality rate comparing to occlusions of other coronary arteries